2019
DOI: 10.1101/2019.12.19.881094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved function of ether lipids and sphingolipids in the early secretory pathway

Abstract: Sphingolipids have been shown to play important roles in physiology and cell biology, but a systematic examination of their functions is lacking. We performed a genome-wide CRISPRi screen in sphingolipid-depleted cells and identified hypersensitive mutants in genes of membrane trafficking and lipid biosynthesis, including ether lipid synthesis. Systematic lipidomic analysis showed a coordinate regulation of ether lipids with sphingolipids, where depletion of one of these lipid types resulted in increases in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Sar1 may locally reduce the bending modulus of the lipid bilayer and facilitate spontaneous positive curvature (Hanna et al, 2016; Lee et al, 2005; Loftus et al, 2012; Settles et al, 2010) thus counter-balancing the growing repulsive forces within the ER lumen as the coat polymerizes (Copic et al, 2012). Moreover, the lipid environment may be locally remodelled with lipid species that facilitate membrane bending or stabilize cargo within the unfavourable conditions of vesicle lumen (Jiménez-Rojo et al, 2019; Melero et al, 2018; Rodriguez-Gallardo et al, 2020). Recruitment of Sec13/Sec31 rods would promote the ordered arrangement of the inner coat (Hutchings et al, 2021; Ma and Goldberg, 2016), thus reducing the bud radius (Gomez-Navarro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sar1 may locally reduce the bending modulus of the lipid bilayer and facilitate spontaneous positive curvature (Hanna et al, 2016; Lee et al, 2005; Loftus et al, 2012; Settles et al, 2010) thus counter-balancing the growing repulsive forces within the ER lumen as the coat polymerizes (Copic et al, 2012). Moreover, the lipid environment may be locally remodelled with lipid species that facilitate membrane bending or stabilize cargo within the unfavourable conditions of vesicle lumen (Jiménez-Rojo et al, 2019; Melero et al, 2018; Rodriguez-Gallardo et al, 2020). Recruitment of Sec13/Sec31 rods would promote the ordered arrangement of the inner coat (Hutchings et al, 2021; Ma and Goldberg, 2016), thus reducing the bud radius (Gomez-Navarro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the lipid environment may be locally remodeled with lipid species that facilitate membrane bending or stabilize cargo under the unfavorable conditions of the vesicle lumen ( Melero et al. , 2018 ; Jiménez-Rojo et al. , 2019 ; Rodriguez-Gallardo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of the co-regulation between SLs and ether PC to maintain the integrity of the secretory pathway [12], we further analyzed the mechanisms of ether lipid changes in CERS2 mutants.…”
Section: Dissection Of Co-regulatory Network With Multiplex Genfmentioning
confidence: 99%
“…This co-regulation leads to membrane lipid compositions that modulate immune responses upon various stimuli [11]. In addition, we recently found that sphingolipids (SLs) and ether phosphatidylcholine (ether PC) are co-regulated, which is critical to maintain the integrity of the secretory pathway [12]. While these studies establish the importance of lipid co-regulation, the mechanisms linking the quantitative change of one lipid to that of another one remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation